“Least Favored Nation”: Pregnancy Discrimination Disparate Impact Claims Post-Young - Lux, Emma (Columbia Journal of Gender and Law, 2022)
This Article analyzes disparate impact claims under the Pregnancy Discrimination Act (PDA) in light of the Supreme Court’s decision in Young v. United Parcel Service, Inc. In Young, the Court interpreted the PDA to provide plaintiffs who bring pregnancy-related disparate treatment claims pursuant to Title VII with additional protections that plaintiffs who bring non-pregnancy-related claims under Title VII do not receive. The Young court reasoned that this interpretation flowed from the PDA because Congress intended the Act to modify Title VII and wanted to ensure that federal courts would not prematurely dismiss pregnancy discrimination claims, as they historically had done. This Article argues that such reasoning not only provides additional protections for plaintiffs who bring disparate treatment claims, but also furnishes similar safeguards for plaintiffs who bring disparate impact claims. The Article concludes by noting, however, that federal courts have not yet extended such special protection to plaintiffs with pregnancy- related disparate impact claims. The result is that courts still often prematurely dismiss their claims, despite the PDA’s purpose and Young’s reasoning.